If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10(1 + -6x) + -74 = 6(3 + -8x) (1 * 10 + -6x * 10) + -74 = 6(3 + -8x) (10 + -60x) + -74 = 6(3 + -8x) Reorder the terms: 10 + -74 + -60x = 6(3 + -8x) Combine like terms: 10 + -74 = -64 -64 + -60x = 6(3 + -8x) -64 + -60x = (3 * 6 + -8x * 6) -64 + -60x = (18 + -48x) Solving -64 + -60x = 18 + -48x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48x' to each side of the equation. -64 + -60x + 48x = 18 + -48x + 48x Combine like terms: -60x + 48x = -12x -64 + -12x = 18 + -48x + 48x Combine like terms: -48x + 48x = 0 -64 + -12x = 18 + 0 -64 + -12x = 18 Add '64' to each side of the equation. -64 + 64 + -12x = 18 + 64 Combine like terms: -64 + 64 = 0 0 + -12x = 18 + 64 -12x = 18 + 64 Combine like terms: 18 + 64 = 82 -12x = 82 Divide each side by '-12'. x = -6.833333333 Simplifying x = -6.833333333
| 5b+3=90+180 | | (6x+5)(4x+12)=0 | | 2y+14=9y | | 5b+3=90 | | h(t)=-4.9t^2+30.5t+9.1 | | 30+2x=3.50x | | (X+2)(x^2+4x+5)= | | 2x-5=9-X | | 358=-0.5x^2+36x-200 | | 6/2-2x=6/4 | | 9(2m+2n+10)= | | m=-6,b=7/3 | | 5x-3=-4+3 | | f(x)=(x^4-32x^3)(4x^2-x) | | 372=-0.5x^2+36x-150 | | 15-(-3)(-x+8)-3= | | 5/2-2x=6/4 | | 3(2x-1)-4(3x-5)=-7 | | 65x+45=50x+30 | | -2+4(5x+2)= | | 32x-.21x=195+12x | | cos(x)+cos(2x)=-1 | | y^2+12y+36=r | | g(-3)=2x^3+2 | | -2x+10=3x+45 | | -2*25+2y=44 | | c/4=1`6 | | 0.03(y-7)+0.14y=0.07y-0.20 | | 9x(2x-4)= | | 3x-9y=-21 | | 13=1-13 | | 27x+14=3(9x-7) |